Added sugar intake and metabolic syndrome in US adolescents: cross-sectional analysis of the National Health and Nutrition Examination Survey 2005–2012. Issue 13 (2nd March 2016) - Rodríguez, Luis A; Madsen, Kristine A; Cotterman, Carolyn; Lustig, Robert H
Abstract: Objective: To examine the association between added sugar intake and metabolic syndrome among adolescents. Design: Dietary, serum biomarker, anthropometric and physical activity data from the US National Health and Nutrition Examination Survey cycles between 2005 and 2012 were analysed using multivariate logistic regression models. Added sugar intake in grams per day was estimated from two 24 h standardized dietary recalls and then separated into quintiles from lowest to highest consumption. Multivariate logistic regression analyses were adjusted for physical activity, age, BMI Z -score and energy intake, and their interactions with race were included. Setting: Nationally representative sample, USA. Subjects: US adolescents aged 12–19 years ( n 1623). Results: Added sugar was significantly associated with metabolic syndrome. The adjusted prevalence odds ratios for having metabolic syndrome comparing adolescents in the third, fourth and fifth quintiles v . those in the lowest quintile of added sugar were 5·3 (95 % CI 1·4, 20·6), 9·9 (95 % CI 1·9, 50·9) and 8·7 (95 % CI 1·4, 54·9), respectively. Conclusions: Our findings suggest that higher added sugar intake, independent of total energy intake, physical activity or BMI Z -score, is associated with increased prevalence of metabolic syndrome in US adolescents. Further studies are needed to determine if reducing intake of added sugar may help US adolescents prevent or reverse metabolic syndrome.